Vegetable Extracts of Azadirachta indica, Argemone mexicana and Soap for the Control of Thrips tabaci and Frankliniella occidentallis in Onion Cultivation - Landa, María del Rosario Rivera; Sánchez, Miguel Aragón; García, Agustín Aragón; Torres, Betzabeth Cecilia Pérez; Peña, Arturo Huerta de la (AGRIVITA Journal of Agricultural Science, 2025)
One of the main pests of onion cultivation worldwide is the thrips complex, mainly Thrips tabaci and Frankliniella occidentalis. These species can decrease the production of this crop, so the objective of this research is to evaluate the effect of the plant extracts of Azadirachta indica and Argemone mexicana and the alternating application of Zote® household soap as a method of controlling the thrips complex in onion cultivation under nursery conditions. Four crop beds were planted, and five treatments were evaluated using four repetitions in a randomized block experimental design. Weekly density sampling of the pest was carried out, and the number of thrips was evaluated before each application. At harvest, the weight of the onion and the size of its leaves were recorded. The results obtained show that plant extracts significantly reduce thrips populations in onions. Additionally, the combination of A. mexicana extract and soap increases crop yield, indicating that this treatment can efficiently control the thrips population in onion cultivation under field conditions.